2017
DOI: 10.1016/j.tifs.2017.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Recent developments in novel shelf life extension technologies of fresh-cut fruits and vegetables

Abstract: Background Fresh-cut fruits and vegetables have gained much more attention worldwide in the past decades. Due to the increased awareness of consumers in sensorial and nutritional qualities of fresh-cut fruits and vegetables, as well as the serious concerns towards public health caused by foodborne outbreaks owing to inappropriate handling or preservation of fresh-cut fruits and vegetables, fresh-cut industry is in urgent need of new and improved technologies for shelf life extension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
164
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 324 publications
(175 citation statements)
references
References 201 publications
(156 reference statements)
2
164
0
9
Order By: Relevance
“…They reported that the reduced POD and PPO activities in the ginger sample treated with OD may be ascribed to lower oxidative stress on the ginger surface due to the antioxidant ability of sucrose concentration. 74 This outcome was in agreement with Ma et al, 79 who stated that the existence of sucrose and ascorbic acid effectively decreased the POD activity in dried-cut cantaloupe melon and other vegetables. Its application as a pretreatment, protects sensory properties and produces food product with minor quality losses.…”
Section: Application Of Od Pretreatmentsupporting
confidence: 88%
“…They reported that the reduced POD and PPO activities in the ginger sample treated with OD may be ascribed to lower oxidative stress on the ginger surface due to the antioxidant ability of sucrose concentration. 74 This outcome was in agreement with Ma et al, 79 who stated that the existence of sucrose and ascorbic acid effectively decreased the POD activity in dried-cut cantaloupe melon and other vegetables. Its application as a pretreatment, protects sensory properties and produces food product with minor quality losses.…”
Section: Application Of Od Pretreatmentsupporting
confidence: 88%
“…With the increasing awareness of consumers on food quality and safety, fresh or minimally processed produce are in high demand (Dasan & Boyaci, 2017). However, fresh produce can serve as a vehicle for a wide range of pathogenic microorganisms and are also susceptible to microbial proliferation due to their high water and nutrient content and the loss of their natural resistance, which is associated with an increase in the number of recorded outbreaks of food borne illnesses and public health scares (Ma, Zhang, Bhandari, & Gao, 2017). For exam-maintain food quality and safety in the food industry, nonthermal physical intervention strategies have received increasing attention from food scientists and manufactures in recent years (Pan, Sun, & Han, 2017;Ramos et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Texture is a significant property of fruit and vegetables, also a primary element affecting sensory aesthetics and food affection in people (Castro & Saraiva, 2014;Ma, Zhang, Bhandari, & Gao, 2017). Traditional heat treatment would destroy the nature histological characteristics of fruit and vegetables, resulting in texture deterioration of the final products (Bordoloi, Kaur, & Singh, 2012; De Roeck, Mols, Duvetter, Van Loey, & Hendrickx, 2010).…”
Section: Introductionmentioning
confidence: 99%